Viral Metagenomics Reveal Blooms of Anelloviruses in the Respiratory Tract of Lung Transplant Recipients - Young, J. C.; Chehoud, C.; Bittinger, K.; Bailey, A.; Diamond, J. M.; Cantu, E.; Haas, A. R.; Abbas, A.; Frye, L.; Christie, J. D.; Bushman, F. D.; Collman, R. G. (American journal of transplantation, 2015)
Few studies have examined the lung virome in health and disease. Outcomes of lung transplantation are known to be influenced by several recognized respiratory viruses, but global understanding of the virome of the transplanted lung is incomplete. To define the DNA virome within the respiratory tract following lung transplantation we carried out metagenomic analysis of allograft bronchoalveolar lavage (BAL), and compared with healthy and HIV+ subjects. Viral concentrates were purified from BAL and analyzed by shotgun DNA sequencing. All of the BAL samples contained reads mapping to anelloviruses, with high proportions in lung transplant samples. Anellovirus populations in transplant recipients were complex, with multiple concurrent variants. Quantitative polymerase chain reaction quantification revealed that anellovirus sequences were 56‐fold more abundant in BAL from lung transplant recipients compared with healthy controls or HIV+ subjects (p < 0.0001). Anellovirus sequences were also more abundant in upper respiratory tract specimens from lung transplant recipients than controls (p = 0.006). Comparison to metagenomic data on bacterial populations showed that high anellovirus loads correlated with dysbiotic bacterial communities in allograft BAL (p = 0.008). Thus the respiratory tracts of lung transplant recipients contain high levels and complex populations of anelloviruses, warranting studies of anellovirus lung infection and transplant outcome. The authors analyze viral sequences in bronchoalveolar lavage fluid from lung transplant recipients using shotgun metagenomics and quantitative PCR, revealing high levels and complex populations of anelloviruses within the lung allografts.